CLINICAL USEFULNESS OF Tc-99m HEXAKIS 2-METHOXYISOBUTYL ISONITRILE GATED SPECT IN PATIENTS WITH DILATED CARDIOMYOPATHY: RETROSPECTIVE ANALYSIS - Khan, Zahid Rahman; Watson, Nat E.; Khan, Afshan Zahid (Journal of Ayub Medical College Abbottabad, 2010)
Background: In Dilated cardiomyopathy the heart is enlarged and ventricles are dilated. Gated myocardial perfusion single photon emission computed tomography is considered state of the art for myocardial perfusion imaging. A retrospective analysis was conducted to evaluate patients with dilated cardiomyopathy with Tc-99m sestamibi gated myocardial perfusion single photon emission computed tomography to evaluate its clinical utility. Methods: A 10 year retrospective medical record review was done from 1991 to 2001 at Wake Forest University, North Carolina, USA. Eligibility criteria included a diagnosis of dilated cardiomyopathy and availability of coronary angiography and Tc-99m sestamibi cardiac imaging results. 26 cases were selected for the final review and inclusion in the study. The study was done with standard protocols for cardiac sestamibi imaging. Results: A total of 26 cases were included in the final analysis. Cases were divided into two main groups. Group-A included 16 patients with no correlation between Tc-99m sestamibi and cardiac catheterisation reports. Group-B included 10 patients with good correlation between the above tests. There were no significant differences between the left ventricular ejection fraction, angina history, sex distribution and diabetic status between the two groups. We applied Wilcoxon Signed Rank Test and z-test to quantify the difference between the two groups. Data was tabulated and z-test was performed. The calculated pvalue was <0.0001. This is significantly less than the tabulated p-value at 5% level of significance, i.e., 1.96. Significant differences exist between Group-A and Group-B. Conclusion: Tc-99m sestamibi is an excellent agent for investigating myocardial perfusion in dilated cardiomyopathy. The reversible and fixed perfusion defects (small to medium sized) seen in dilated cardiomyopathy after performance of Tc-99m sestamibi gated single photon emission computed tomography imaging may not be due to coronary artery disease. Tc-99m sestamibi single photon emission computed tomography is useful as a routine non-invasive technique to evaluate myocardial function in dilated cardiomyopathy. Keywords: Gated single photon emission computed tomography, dilated cardiomyopathy, sestamibi, positron emission tomography